Coalescence and Collisions of Gold Nanoparticles - Antúnez García, Joel; Mejía Rosales, Sergio; Pérez Tijerina, Eduardo; Montejano Carrizales, Juan Martín; José Yacamán, Miguel (2011)
We study the assembling of small gold clusters subject to collisions and close contact coalescence by using molecular dynamics simulations to simulate events that occur typically in the sputtering process of synthesis. Our results support the notion that the kinetics of coalescence processes strongly determine the geometry and structure of the final particle. While impact velocities, relative orientations, and the initial shape of the interacting particles are unlikely to strictly determine the structural details of the newly formed particle, we found that high initial temperatures and/or impact velocities increase the probability of appearance of icosahedral-like structures, Wulff polyhedra are likely to be formed as a product of the interactions between nanospheres, while the appearance of fcc particles of approximately cuboctahedral shape is mainly due to the interaction between icosahedra.